Consumers' purchase intention of halal food at food courts: the moderating role of halal certification / Muhammad Abdul Adib Abd Aziz - Abd Aziz, Muhammad Abdul Adib (2022)
Halal food and beverage has risen to prominence as a global leader in Islamic lifestyle spending. The increasing global demand for halal food highlights the importance of halal certification. Other fundamental issues related to halal food, such as hygienic practise, halal certificate manipulation, and expiration, have contributed to consumer concern with reports of misconduct and unethical behaviour. This includes all types of eateries such as restaurants, kiosks, cafeterias, food courts, etc. As a result, the Decomposed Theory of Planned Behaviour was used in this study to understand the relationship between the consumer's intention for halal food at food courts. First, this study investigated at how consumers' attitudes toward halal food purchasing at food courts were influenced by their knowledge, halalan thoyiban, and lifestyle. The study then looked at the impact of family and friend influence, as well as media influence, on consumers' subjective norms toward halal food purchasing at food courts. Third, the study sought to ascertain the impact of self-efficacy and facilitating conditions on consumers' perceived behavioural control when purchasing halal food at a food court. Fourth, this study found that attitude, subjective norms, and perceived behavioural control all have an impact on consumers' intentions to buy halal food at food courts. The study then investigated the influence of halal certification on customer buying intentions. Finally, the influence of attitude, subjective norm, and perceived behavioural control on consumer intention to purchase halal food at food courts was investigated using halal certification as a moderating variable. Self-administered questionnaires were used to distribute the surveys at food courts in Klang Valley shopping malls. As a result, 394 people who had eaten at those food courts filled out the survey. The data was analysed using the Statistical Package for Social Science (SPSS) and PLS Software. Nine of the 14 hypotheses tested were supported. The findings revealed that knowledge, halalan thoyiban, and lifestyle have a significant influence on attitudes toward halal food consumption. The influence of family and friends, as well as the influence of the media, significantly influenced subjective norm, and self-efficacy and facilitating conditions significantly influenced perceived behavioural control. However, it was discovered that perceived behavioural control was insignificant in influencing consumer intention to purchase halal food, whereas attitude and subjective norms were significant. Furthermore, halal certification was found to be insignificant in terms of influencing consumers' purchase intentions. Furthermore, the findings revealed that halal certification had no effect on the relationship between attitude, subjective norm, or perceived behavioural control and consumers' purchase intention of halal food. The findings of this study added to the body of knowledge about halal certification as well as the other constructs studied. More importantly, it provided academics and industry with some insights into improving consumer purchase intentions of halal food at food courts.